Bitter Taste Responses of Gustducin-positive Taste Cells in Mouse Fungiform and Circumvallate Papillae - Yoshida, Ryusuke (Neuroscience, 2017)
Bitter taste serves as an important signal for potentially poisonous compounds in foods to avoid their ingestion. Thousands of compounds are estimated to taste bitter and presumed to activate taste receptor cells expressing bitter taste receptors (Tas2rs) and coupled transduction components including gustducin, phospholipase Cβ2 (PLCβ2) and transient receptor potential channel M5 (TRPM5). Indeed, some gustducin-positive taste cells have been shown to respond to bitter compounds. However, there has been no systematic characterization of their response properties to multiple bitter compounds and the role of transduction molecules in these cells. In this study, we investigated bitter taste responses of gustducin-positive taste cells in situ in mouse fungiform (anterior tongue) and circumvallate (posterior tongue) papillae using transgenic mice expressing green fluorescent protein in gustducin-positive cells. The overall response profile of gustducin-positive taste cells to multiple bitter compounds (quinine, denatonium, cyclohexamide, caffeine, sucrose octaacetate, tetraethylammonium, phenylthiourea, L-phenylalanine, MgSO(4), and high concentration of saccharin) was not significantly different between fungiform and circumvallate papillae. These bitter-sensitive taste cells were classified into several groups according to their responsiveness to multiple bitter compounds. Bitter responses of gustducin-positive taste cells were significantly suppressed by inhibitors of TRPM5 or PLCβ2. In contrast, several bitter inhibitors did not show any effect on bitter responses of taste cells. These results indicate that bitter-sensitive taste cells display heterogeneous responses and that TRPM5 and PLCβ2 are indispensable for eliciting bitter taste responses of gustducin-positive taste cells.